Surface markers and size of lymphocytes in human umbilical cord blood stimulated into deoxyribonucleic acid synthesis by Epstein-Barr Virus. - Robinson, J (1979)
We characterized subpopulations of lymphocytes in human umbilical cord blood which are stimulated into deoxyribonucleic acid synthesis by Epstein-Barr virus. Lymphocytes were examined simultaneously for deoxyribonucleic acid synthesis by autoradiography and for surface markers by rosette formation with sheep erythrocytes or erythrocytes coated with antibody and mouse complement (EAC). The subpopulation which incorporated [3H]thymidine after exposure to virus consisted mainly of cells which formed rosettes with EAC. Lymphocytes were enriched or depleted of thymus-derived lymphocytes (T cells), null cells, or cells forming rosettes with EAC. The extent of sensitivity of the cells to stimulation by Epstein-Barr virus correlated with the proportion of the population which formed rosettes with EAC. When mononuclear cell populations were depleted of T lymphocytes and then fractionated by size, small lymphocytes showed higher rates of deoxyribonucleic acid synthesis after virus exposure and higher transformation frequency than did larger cells or unfractionated cells. Thus, the cells which are stimulated into deoxyribonucleic acid synthesis by Epstein-Barr virus appear to be the same as cells which are ultimately transformed.